Chorion exploration in the tribe Anthocharidini (Lepidoptera: Pieridae) and their possible importance in its systematics - Nieves-Uribe, Sandra; Flores-Gallardo, Adrián; Llorente-Bousquets, Jorge (Zootaxa, 2020)
We describe and compare the morphology of the chorion in nine species belonging to five genera of the tribe Anthocharidini (Pieridae: Pierinae), from a sample of 12 females with mature eggs, the bibliographic record of oviposited eggs, and photographs of scanning electron microscopy (SEM). The eggs examined come from Mexico, Spain, Brazil and Costa Rica. Its characterization was made considering the main structural features of the chorion in this tribe; it includes a distinction of structures in the apical zone and differentiation between the chorionic regions. We attached to this work sheets, diagrams, and terminology to understand and clarify the descriptions. Our results agree with the proposal of Anthocharidini as the least derived tribe of the Pierinae, considering that Hebomoia, a specialized genus, is not part of it. Tribes such as Leptosiaini, Elodinini or Nepheroniini also have more chorionic characteristics related to more derived tribes of the Pierinae.